Conservation agreements and environmental governance: The role of nongovernmental actors. Issue 1 (9th November 2020) - Boonrueang, Surasak; Reid, Colin
Abstract: This article explores how conservation agreements can be used to examine the trend towards environmental governance by multiple players, where nongovernmental bodies play a part in environmental regulation. The laws authorizing the creation of a conservation agreement in three jurisdictions, namely New South Wales (Australia), Scotland (United Kingdom) and Maine (United States), move away from regulation by government, where governmental bodies play the pivotal role in environmental governance, towards governance by multiple players. This article illustrates how the different legal features regarding who can create, oversee and enforce a conservation agreement reflect different styles and levels of engagement in environmental regulation. The Australian law represents a model of nature conservation heavily relying on governmental regulation. This is different from the United States model, where nongovernmental bodies play a significant role in the burgeoning use of conservation agreements. The Scottish model is placed somewhere between those in that while it confers the primary role on specified governmental bodies, some nongovernmental conservation bodies can in some circumstances be designated to fulfil the same function. The different levels of participation by governmental and nongovernmental bodies discussed in this article reveal strengths and weaknesses in involving different ranges of actors in environmental governance and point to lessons as other jurisdictions consider embracing conservation agreements to support their conservation policy.